2023
DOI: 10.3390/vaccines11020477
|View full text |Cite
|
Sign up to set email alerts
|

BNT162b2 COVID-19 Vaccine Safety among Healthcare Workers of a Tertiary Hospital in Italy

Abstract: Millions of people have died because of the COVID-19 pandemic. The vaccination campaign helped tackle the pandemic and saved millions of lives. In a retrospective pharmacovigilance study, we explored the safety of the BNT162b2 (Comirnaty) vaccine among healthcare workers (HCWs) in a large Italian teaching hospital, and 2428 Adverse Events Reports (AERs) filed by HCWs after the administration of the first dose of vaccine were collected and analyzed, reporting the results quantitively and comparing them to the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Among those participants experiencing any AEFI in our study, majority (119, 99.0 %) experienced only mild/minor grade AEFI with only 2(1.0 %) experiencing a severe AEFI requiring hospitalization but without any sequelae or long-term complication. Similar results were reports by other studies from various parts of India [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] and across the globe [29] , [30] , [31] , [32] , [33] . In the study by Kamal et al [22] , two serious AEFI (altered sensorium) were reported within 48 h after the 1st dose of COVISHIELD TM vaccine.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among those participants experiencing any AEFI in our study, majority (119, 99.0 %) experienced only mild/minor grade AEFI with only 2(1.0 %) experiencing a severe AEFI requiring hospitalization but without any sequelae or long-term complication. Similar results were reports by other studies from various parts of India [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] and across the globe [29] , [30] , [31] , [32] , [33] . In the study by Kamal et al [22] , two serious AEFI (altered sensorium) were reported within 48 h after the 1st dose of COVISHIELD TM vaccine.…”
Section: Discussionsupporting
confidence: 90%
“…Kadali et al [29] assessing the side effects of BNT162b2 mRNA COVID-19 vaccine reported soreness, fatigue, myalgia, headache, chills, fever and joint pain as the most commonly reported symptoms. In the study by Beccia et al [33] from Italy three clusters of adverse effects defined by the presence/absence of fatigue, malaise, localized pain, chills, pyrexia, insomnia, nausea and injection site pain, were frequently reported together.…”
Section: Discussionmentioning
confidence: 99%